LOW-CEMENT DOSAGE REFRACTORY CONCRETE WITH LOW THERMAL CONDUCTIVITY - LUCIAN PAUNESCU; ENIKO VOLCEANOV; BOGDAN-VALENTIN PAUNESCU; IOANA MONICA SURUGIU (Journal of Engineering Studies and Research)
Super-aluminous refractory concrete (over 94 % Al2O3) with low dosage of cement (9 %) was made, its physical, thermal, and mechanical characteristics being considered suitable for the intermediate layer of a steel casting ladle: porosity of 29.31 %, the apparent density of 2.32 g·cm-3 thermal conductivity of 1.45 W·m-1·K-1, and compressive strength of 34.8 MPa (after heat treatment at 1500 ºC). The aim of the research was achieving a super-aluminous concrete with low-cement dosage, which would have acceptable thermal insulation properties, so that the heat loss through this refractory lining layer would be significantly reduced compared to the reference situation.